Efek Mediasi Penggunaan Financial Technology Pada Pengaruh Literasi Keuangan Dan Inklusi Keuangan Terhadap Keputusan Investasi Generasi Milenial Di Dki Jakarta - Nurjamil; Tugiantoro; Ida Adhani (Politeknik Raflesia Press, 2025)
The aim of this research is to examine the influence of financial literacy and financial inclusion on investment decisions mediated by the use of financial technology. This research is quantitative research with data collection techniques using questionnaires and literature study. Variable measurement uses the Likert Scale technique with a weight scale from 1 to 5. The sample selected as respondents for this research was 100 people, from the total number of millennial generations in DKI Jakarta using the purposive sampling method. The data processing method in this research is structural equation modeling (SEM). The research results show that: 1) Financial literacy has a positive effect on investment decisions. 2) financial inclusion has a positive effect on investment decisions. 3) Financial technology has a positive influence on investment decisions. 4) Financial literacy has a positive effect on financial technology. 5) Financial inclusion has a positive effect on financial technology. 6) Mediating financial technology to influence financial literacy on investment decisions. 7) mediate financial technology to influence financial inclusion on investment decisions.